SALT-DOME STRUCTURES MODELING IN DEPTH DOMAIN USING RAY TRACING AND SEISMIC ATTRIBUTE ANALYSIS - RUSACHENKO, Natalia; PASTUSHENKO, Tetiana; VYZHVA, Serhii (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Background. Increasing the resource base and hydrocarbon exploration is the main goal of performing seismic data acquisition. Due to the presence of salt diapirs, normal and reverse faults as well as other discontinuities in the geological subsurface, there appear characteristic features of seismic signals – a break in phase continuity and significant attenuation of the amplitude without a break in phase continuity. These geological features are sometimes distinguished by attenuation of the seismic signal or even an absence of wave field reflections. In areas of salt-dome tectonics, it is often completely impossible to trace any reflective horizons. To accurately map the fault location, deep or vertical horizons, it is necessary to improve the approach to obtaining and interpreting data in faulted areas with complex geology.Methods. The research presents an integrated approach to modeling the rays from each receiver of seismic signals to each bin on the reflective boundary. The reflected beams then propagate from the reflective boundary to the simulated position of the seismic receiver. Since the nature and velocity of beam propagation vary, it is possible to obtain additional information from zones shielded by faults or sub-vertical horizons, to trace the trajectories of seismic energy propagation and its focusing/defocusing zones. Verification of the seismic image and its geological content was performed using seismic attribute analysis.Results. Ray tracing allowed analyzing poor illumination zones below salt wings. During further steps such as processing and interpretation, ray tracing provided additional information for diapir mapping. Seismic attribute analysis was used as an additional tool to define the boundaries of the salt structure. This makes it possible to analyze the dynamic and kinematic parameters of the seismic field and map the salt body's boundaries based on these characteristics.Conclusions. An integrated approach involving several methods will solve the problem of mapping seismic horizons in areas surrounding fault zones with a weak seismic signal. A more reliable geological image can only be obtained by using complex sequences, including seismic processing, ray tracing, and seismic attribute analysis. The integrated application of the techniques demonstrates consistent geological results and has implications for discovering new deposits and hydrocarbon traps confined to the zones of development of salt-dome tectonics in the Dnipro-Donets basin.
Keywords: ray tracing; seismic data processing; seismic attribute analysis; interpretation; salt tectonics; diapir; hydrocarbons; oil; gas